17-alpha hydroxyprogesterone caproate and risk for venous thromboembolism during pregnancy. (12th December 2022) - Schuster, Meike; Ananth, Cande V.; Gomez, Daniela; Huang, Yongmei; Gyamfi-Bannerman, Cynthia; Wright, Jason D.; D'Alton, Mary E.; Friedman, Alexander M.
Abstract: Introduction: 17-alpha hydroxyprogesterone caproate (17 P) is a progestin commonly used during pregnancy to reduce risk of recurrent preterm birth. History of thromboembolism is a contraindication to 17 P and the package insert for 17 P recommends discontinuation in the setting of an acute VTE event. The objective of this study was to determine whether 17 P is associated with increased risk of VTE. Study Design: The MarketScan claims database was used to perform a retrospective cohort of women who underwent delivery from 4/2008 to 1/2015. We identified women who received 17 P during pregnancy based on pharmacy benefits. Risk for VTE including deep vein thrombosis, pulmonary embolism, or both was stratified based on the presence or absence of 17 P pharmacy receipt. Both antenatal and delivery hospitalization VTE events were asceratined and these periods were analyzed individually. Relative risk (RR) was determined based on 17 P receipt. Results: Among 4, 775, 667 delivery hospitalizations, 18, 745 women received 17 P. Among women who did not receive 17 P, 0.52% of women ( n = 24, 529) had a VTE diagnosis compared to 0.61% ( n = 114) receiving 17 P (RR 1.18, 95% CI 0.98–1.42). Comparing VTE events (i) during the antenatal period and (ii) during delivery hospitalizations, risks did not differ significantly for patients receiving 17 P. When risk was restricted to the cohort of patients without a diagnosis of a prior VTE event, 0.30% of women ( n = 56) receiving 17 P were diagnosed with an event versus 0.28% of women ( n = 13, 427) not receiving 17 P (RR 1.07, 95% 0.82–1.39). Discussion: No significant increased risk for VTE was noted with 17 P receipt. While new research has led to reconsideration of clinical use of 17 P for preterm birth prevention based on efficacy, findings from this analysis do not support major risk for thrombosis.